Complementary and alternative medicine use in coronary heart disease patients: a cross-sectional study from Palestine - Abdelraouf O. Salah; Ahmad D. Salameh; Mohanad A. Bitar; Sa’ed H. Zyoud; Abdulsalam S. Alkaiyat; Samah W. Al-Jabi (BMC Complementary Medicine and Therapies, 2020)
Abstract Background There is a lack of data on the use of complementary and alternative medicine (CAM) in patients with coronary heart disease (CHD). This study examined the use of CAM among patients with CHD, the reasons and factors influencing their use, the types of CAM used, and the relationship between patient’s demographics and the use of CAM. Methods In order to determine the prevalence and usage of CAM among Palestinian patients with CHD, a cross-sectional descriptive study was performed from three different hospitals. Using a convenient sampling method, a questionnaire was completed in a face-to-face interview with the patients. Descriptive statistics were used for socio-demographic, and clinical variables. Siahpush scale was used to examine the attitude of CHD patients toward CAM use. Results Of the 150 patients that were interviewed, 128 (85.3%) of the patients completed the questionnaire. The majority of CAM users reported CAM use for health problems other than CHD, while a total of 59 (45.9%) patients have used CAM for their heart problems. On the other hand, it was found that the place of residency and pattern of CHD were significantly associated with CAM use (p = 0.039 and 0.044, respectively). In addition, religious practices were found to be the most common form of CAM used by patients, while body and traditional alternative methods were the least being used. A significant association between the attitudes of patients with CHD and their use of CAM was found (patients’ attitudes towards alternative medicine and natural remedies were p = 0.011 and 0.044, respectively). Conclusions CAM use among our respondents is common. Despite a lack of evidence-based research supporting its potential benefits and side effects. Understanding the factors that affect CAM use by CHD patients offers healthcare workers and policymakers an opportunity to better understand CAM use and ultimately improve patient-physician interactions.